Walkability: a bibliometric analysis - Richard Pitilin, Taiany (2020)
Urban mobility in cities has presented several problems. Cyclists and pedestrians face challenges to get space to move along with motor vehicles that are gaining more and more space in cities. The walkability can be an important tool for assessing how attractive the environment is for pedestrians. This article seeks to contribute to an understanding of the paths that the scientific production on walkability has been taking in the last years presenting a bibliometric analysis referring to the period of the years between 2000 and 2018. The results show the analyses of 1,112 publications according to their quantitative evolution during the time period and their contributions by country and by researcher. It can be verified that the research on walkability is on the rise and that the United States is ranked as the country with the most publications in the area.